Flood Control Management for the City and Surroundings of Jeddah, Saudi Arabia - Al Saud, Mashael (Springer, 2015)
During the past years, Saudi Arabia has been affected by particularly severe torrential rains and floods. This book presents an in-depth and all-encompassing study on the floods that occurred in the Jeddah area in 2009 and 2011, including water-flow mechanisms, state-of-the-art techniques for flood assessment, flood control and appropriate management approaches. It highlights a number of methods and concepts that can be applied in similar areas in Saudi Arabia in order to reduce and mitigate the impact of torrential rains and floods.